Vol 16 No 1 (2022) PENGARUH EKSPOR PRODUK HANDICRAFT TERHADAP PENINGKATAN PENDAPATAN PERAJIN DAN IMPLIKASINYA TERHADAP PEMBANGUNAN NASIONAL - Dr. Winaya Purwanti, SE.,MM Dr. Winaya Purwanti, SE.,MM; Achmad Jaelani Achmad Jaelani (LPPM Swadaya Institute of Business and Communication, 2022)
Exports and investment play an important role in the economic activity of a country. Exports will generate income that will be used to finance the import of capital goods and raw materials required in the production process that will create value added. Aggregation of value added generated by all units of production in the economy is the value of the Gross Domestic Product (GDP). Handicraft is one of the sub-sectors of creative industries. Indonesia is rich in a variety of handicraft done by many people and many take advantage of local raw materials. In fact, the potential to be the mainstay of handicraft products to compete in the global marketplace. The research approach refers to the Cobb-Douglas production function. In connection with the paradigm of macroeconomic theory, the theory of production can be seen from the end of a maximized output in an economy is through the Gross Domestic Product (GDP). To declare a function Coob-Dauglas production in linear form, the production function is transformed in log-linear form is common in econometric analysis. The analysis in this study using multivariate regression with software tools Eviews7. The results were: 1) In simultaneous and partial GDP USA, Middle Rate USD, BOP Indonesia, Shopping ICT / IT, education spending has a significant effect on handicraft exports and GDP partially USA, Middle Rate USD, and Shopping ICT / IT impact positive and significant impact on exports of handicraft products but BOP Indonesia and Shopping Education has no significant positive effect on exports of handicraft products. 2) Export of handicraft products have a positive and significant effect on income of craftsmen. 3) Export of handicraft products and Revenue Craftsmen significant effect on Indonesia's GDP and 4) Export of handicraft products directly influence the income artisans and handicraft exports also affects indirectly through income artisans as intervening significantly to the GDP of Indonesia.